Is there any association among depressive symptoms, job satisfaction and self-assessed empathy? A correlational study in Greek Psychiatric/Mental Health Nurses - Karanikola, Maria; Zartaloudi, Afroditi; Nystazaki, Maria; Zavrou, Rafailia; Papathanassoglou, Elizabeth (My University, 2020)
A descriptive correlational design was applied to explore association among self-assessed depressive symptoms, job satisfaction and self-assessed empathy in 206 Greek Psychiatric-Mental Health Nursing Personnel (PMHNP). Depressive symptom intensity was associated with satisfaction from performed tasks (r = -0.157, p = 0.033), professional prestige (r = -0.255, p < 0.0001), relations with colleagues (r = -0.263, p < 0.0001) and empathy (r = -0.183, p = 0.013). In a regression model, only satisfaction from relations and workload remained significant depressive symptom predictors after controlling for important covariates. The quality of relations with colleagues and workload are important predictors of PMHNPs self-perceived mental health well-being, independently of clinicians' self-assessed empathy or overall professional satisfaction.
Keywords: Communication; Depression; Distress; Greece; Job satisfaction; Nurses; Perspective taking; Psychiatric symptoms; Therapeutic relationship